Predicting feedlot cattle performance from intake of dry matter and NEg early in the feeding period - Silvestre, A. M. [UNESP]; Cruz, G. D.; Owens, F. N.; Pereira, M. C.S. [UNESP]; Hicks, R. B.; Millen, D. D. [UNESP] (Elsevier, 2019)
The objectives of this study were: 1) To identify which specific week or weeks at the beginning of feeding period was most closely correlated with intake of net energy for gain (NEg) and dry matter (DM) for the full feedlot period of 140–180 d, and 2) to determine how various performance measurements were correlated with intake during this selected time frame. The database was compiled from one commercial feedlot, contained 2,495 pens of steers and 1,637 pens of heifers representing a total of 485,458 animals. Diets had similar composition across a 6 years period. Responses in intake of DM and NEg for the full finishing period were tested separately by including gender, initial body weight (BW) and days on feed as covariates in PROC NLIN of SAS. The PROC CORR was used to determine the correlation between intakes of DM and NEg early in the feedlot period with intake of DM and NEg for the entire finishing period. Intake periods of interest included individual weeks or the combination of weeks 5–12. Among the individual weeks, intakes of DM and NEg during week 7 were correlated most closely with intakes of DM and NEg across the entire finishing period for steers (r = 0.72) and heifers (r = 0.66). Based on mean DM intake during week 7, pens were grouped into quartiles: Top, High, Lower and Lowest. Pens of steers and heifers within the Top ¼ group during week 7 had greater (P < 0.05) final BW and average daily gain (ADG) across the full feeding period than pens of steers and heifers in other quartiles. However, G:F for steers within the Top ¼ group was lower than for pens in the Lower ¼ and Lowest ¼ groups. Pens of cattle within the Lowest ¼ group had more sick head days (P < 0.05) and greater death loss (P < 0.05) than pens of cattle of the Top ¼ group. Pens of cattle within the Top ¼ group had greater (P < 0.05) week-to-week DM intake fluctuation expressed in kg for both steers and heifers. Mean DM intake during week 7 can be utilized as an index to detect pens with the greatest potential of ADG and should help to identify pens with health or management anomalies so that proper corrective actions might be taken.
Keywords: Dry matter intake; Energy; Feedlot; Heifers; Performance; Steers